2019
DOI: 10.1080/00336297.2018.1551807
|View full text |Cite
|
Sign up to set email alerts
|

A Position Statement on Social Justice, Physical Education, and Bullying: A Figurational Sociological Perspective

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…A systematic search of studies that reported the effect of overweight/obesity (in the form of body mass index. The most significant finding was that the higher the victim of physical bullying, the higher the emotional impulsiveness and aggressiveness of a child (Mierzwinski, Cock, & Velija, 2019). Here, students feel threatened or attacked easily and unable to control the behavior of victim's feelings which results in disrupting the capacity of self-assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic search of studies that reported the effect of overweight/obesity (in the form of body mass index. The most significant finding was that the higher the victim of physical bullying, the higher the emotional impulsiveness and aggressiveness of a child (Mierzwinski, Cock, & Velija, 2019). Here, students feel threatened or attacked easily and unable to control the behavior of victim's feelings which results in disrupting the capacity of self-assessment.…”
Section: Discussionmentioning
confidence: 99%
“…When presenting the profile of a perpetrator of bullying in physical education, it should be noted that according to the ETMD, different factors cause students to use violence against their peers (Cicchetti & Lynch, 1993;Overstreet & Mazza, 2003). Bullying in physical education often takes place within a peer-group setting (Mierzwinski et al, 2019), and peer support (or lack thereof) given to the perpetrator may support or inhibit their behavior.…”
Section: Peer Support Weight Status Gender Age and Being A Perpetrato...mentioning
confidence: 99%
“…This aligns with Journal of Interpersonal Violence other studies concerning bullying in physical education (e.g., Vianna et al, 2015) and other areas of an adolescent's life in Poland (Mazur et al, 2017), which have found that direct bullying is more common among younger students. This might result from socialization processes and the ability to control emotional impulses and aggression increasing with age (Mierzwinski et al, 2019).…”
Section: Age and Being A Victim Or Perpetrator Of Bullying In Physica...mentioning
confidence: 99%
“…Elias's collaborations with Dunning on sports, violence and leisure led to broader reflections on changing attitudes to social identities, power relations and the exclusion of certain bodies in physical education. Mierzwinski et al (2019) is one such example, providing a long-term historical perspective on sports development and gendered power relations. Importantly, the authors draw attention to the fact that growing sensitivities to violence and other forms of morally transgressional behaviour have led to heightened expectations surrounding the shaming of bullies.…”
Section: An Eliasian Approach To School Climate and Peer Harassmentmentioning
confidence: 99%